Outlooks and insights on group decision and negotiation : 15th International Conference, GDN 2015, Warsaw, Poland, June 22-26, 2015, Proceedings /: 15th International Conference, GDN 2015, Warsaw, Poland, June 22-26, 2015, Proceedings. (2015) - Unknown
No abstract available